Optimasi Rute Distribusi ES Kristal Dengan Metode NN Dan LS UMKM XYZ - Husin, Salmawati; Lahay, Idham Halid; Uloli, Hendra (Jurnal Teknik, 2025)
This study aims to optimize distribution routes for Micro, Small, and Medium Enterprises (MSMEs) engaged in the production of premium ice crystals. The Nearest Neighbor (NN) method is used to find the initial route by selecting the closest locations in sequence, while Local Search is used to improve the route found by searching for better local solutions through exchange or improvement of the delivery sequence. The testing was conducted using distribution data from several customers and delivery locations. The research results show that the distribution route for UMKM Es Kristal Premium, when applying the Nearest Neighbor and Local Search methods, resulted in a reduction in delivery distance from 40.3 km to 3.74 km, with a savings of 16.28% for the urban area, and from 52.5 km to 33.1 km for the Limboto-Telaga area, with a savings of 36.95%. Additionally, this method also reduces transportation costs, with initial transportation costs of Rp. 100,000.00 decreasing to Rp. 66,840.00, representing a cost reduction of 33.16%. This method can optimize time and operational cost savings, which can have a positive impact on UMKM Es Kristal Premium in enhancing their competitiveness and service to customers.